A Peep into Purple Medicine (GAIMS Journal of Medical Sciences, 2024)
The colors have role in diagnosis and treatment of diseases. A change in color of skin or urine may indicate the underlying pathological alterations in body. Similarly, a change in visual color perception may be an early indicator of neuropsychological disorder requiring medical attention. In addition, colors affect the perceived effect (beneficial or adverse) of a drug and thus influence the effectiveness of a drug. In an experiment, 100 medical students were given blue or pink placebo in the garb of sedative or stimulant medicine respectively. Subjects taking the blue placebos felt less alert (66%) than those taking the pink (26%) and also drowsier. Studies show that red, yellow, and orange drug formulations are perceived as stimulant whereas blue and green as tranquillizing drugs. The sildenafil is known world over as “the Blue Pill” because blue refers to calmness and tranquility. Interestingly, its use may result in difficulty in discriminating colors such as blue, purple, and green. The purple color is a secondary color, a mix of two primary colors red and blue. The purple color symbolizes calm, creativity, dignity, frustration and sadness, luxury, magic, and mysticism and power. Poetically, it signifies love. The purple-heart epitomizes love, trust, and support. ‘A purple patch in once life’ is an idiom to narrate a period of exceptional success or good luck. In Feng Shui, purple color emanates high vibrations and is used sparingly. Excess use can promote depression! The “Porphura” is the ancient Greek word for purple. It originates from the purpura mollusk, which produces a purple substance used to dye the royal clothes.